Exploration of antimicrobial potential of essential oils of Cinnamomum glanduliferum, Feronia elephantum, Bupleurum hamiltonii and Cyclospermum leptophyllum against foodborne pathogens. (13th September 2013) - Singh, Charu; Singh, Shalini; Pande, Chitra; Tewari, Geeta; Pande, Veena; Sharma, Pratibha
Abstract: Context : Cinnamomum glanduliferum (Wall.) Meissn. (Lauraceae), Feronia elephantum Correa (Rutaceae), Bupleurum hamiltonii Balak (Apiaceae) and Cyclospermum leptophyllum (Pers.) Sprague ex Britton & P. Wilson (Apiaceae) are common species found in Northwest Himalaya and are widely used as folk medicine. The study became more interesting because hitherto there are no reports on the antimicrobial screening of these species with specific chemical composition. Objective : The antimicrobial potential of the essential oils of C. glanduliferum, F. elephantum, B. hamiltonii and C. leptophyllum against some commonly occurring foodborne pathogenic and spoilage bacteria was explored in this study. Materials and methods : Antimicrobial screening studies of essential oils were performed against some Gram-positive and Gram-negative bacterial strains using broth-dilution methods. Each essential oil was prepared by serial double dilution method to get final concentrations ranging from 0.85--440.0 µg/ml in a 96 microtiter plate. Results : The in vitro studies revealed that C. glanduliferum oil was very active against Gram-negative bacteria, A. salmonicida (MIC 1.72 µg/ml), E. coli (MIC 3.43 µg/ml), and P. aeruginosa (MIC 3.43 µg/ml) as compared to the standards gentamicin and kanamicin. Oil of C. leptophyllum exhibited better inhibitory activity profile against Gram-positive S. aureus (MIC 3.43 μg/ml) and Gram-negative E. herbicola (MIC 1.72 μg/ml) and P. aeruginosa (MIC 3.43 μg/ml) as compared to the standards. Discussion and conclusion : These results reveal that these essential oils may be used in the treatment of diseases caused by the foodborne pathogenic and spoilage bacteria. Their importance as potential medicinal agents is based on the antimicrobial findings.